2020
DOI: 10.1093/narcan/zcaa001
|View full text |Cite
|
Sign up to set email alerts
|

Putatively cancer-specific exon–exon junctions are shared across patients and present in developmental and other non-cancer cells

Abstract: This study probes the distribution of putatively cancer-specific junctions across a broad set of publicly available non-cancer human RNA sequencing (RNA-seq) datasets. We compared cancer and non-cancer RNA-seq data from The Cancer Genome Atlas (TCGA), the Genotype-Tissue Expression (GTEx) Project and the Sequence Read Archive. We found that (i) averaging across cancer types, 80.6% of exon–exon junctions thought to be cancer-specific based on comparison with tissue-matched samples (σ = 13.0%) are in fact presen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 44 publications
(52 reference statements)
1
14
0
Order By: Relevance
“…David et al (2020) extended the analysis of exon-exon junctions to 10,549 tumor samples across 33 TCGA cancer types and observed that more than 50% of new junctions were not shared among cancer samples. Importantly, in cervical cancer they identified a total of 14,086,434 exon-exon junctions of which 2,263,326 were specific to cervical cancer (David et al, 2020).…”
Section: Deregulation Of the Splicing Machinery In Cancermentioning
confidence: 99%
“…David et al (2020) extended the analysis of exon-exon junctions to 10,549 tumor samples across 33 TCGA cancer types and observed that more than 50% of new junctions were not shared among cancer samples. Importantly, in cervical cancer they identified a total of 14,086,434 exon-exon junctions of which 2,263,326 were specific to cervical cancer (David et al, 2020).…”
Section: Deregulation Of the Splicing Machinery In Cancermentioning
confidence: 99%
“…We benchmarked SICILIAN using three different types of data: matched bulk and scRNA-seq data from five human lung adenocarcinoma cell lines 17 , simulated data with known grown truth 9,18 , and real scRNA-seq data, where we ran SICILIAN on 36,583 lung cells from two individuals from the human lung cell atlas (HLCA) 16 and 16,755 lung cells from two individuals from the mouse lemur cell atlas (MLCA) studies, all sequenced using the 10x platform. We compared SICILIAN to commonly used filtering criteria in the field: all junction calls based on STAR 13 raw alignments, the junctions supported only by uniquely mapping reads 19 , and calling junctions based on read counts 20,21 .…”
mentioning
confidence: 99%
“…The importance of the latter was highlighted by David et al, [ 55 ] through analyses of splicing events in cancer and non-cancer RNA-seq data from The Cancer Genome Atlas, the Genotype-Tissue Expression Project, and the Sequence Read Archive. The result of this analysis demonstrated that simply comparing cancer samples to the matched normal tissue from which cancer derives, in that absence of considering other tissue types and developmental time points, results in erroneously identified cancer-specific neojunctions.…”
Section: T Cell-mediated Immunitymentioning
confidence: 99%